Interaction of Toxoplasma gondii with human brain microvascular endothelial cells in vitro - Al-sandaqchi, Alaa (2016)
Background: The brain is the most commonly affected organ during Toxoplasma gondii infection but the mechanisms utilized by this protozoan parasite for disrupting the brain's endothelial cells lining the blood–brain barrier (BBB) and moving to invade the brain are not yet understood. In the present study, we investigated the cellular pathogenicity of T. gondii infection in human brain microvascular endothelial cells (HBMECs), a fundamental component of the BBB. Methods: Intracellular development of T. gondii tachyzoites within HBMECs was characterized by using Acridine Orange (AO) staining. The integrity of HBMECs moolayer and tight junction permeability during T. gondii infection were assessed using transendothelial electrical resistance (TEER). Morphological changes associated with infection was assessed by scanning electron microscopy (SEM) and transmission electron microscope (TEM). Cell viability and metabolic changes associated with infection were identified using alamar blue and nuclear magnetic resonance (1H NMR). The changes in lipid content and fatty acid composition of the total phospholipids were evaluated using LipidTox staining and gas chromatography (GC). The changes in the content of trace elements in response to T. gondii infection was assessed using inductively coupled plasma mass spectrometry (ICP-MS). Results and Discussion: The invasion, growth, and replication of T. gondii tachyzoites within HBMECs are possible, with disruption of the integrity and viability of the host cell through the course of infection. AO staining of T. gondii tachyzoites infecting HBMECs showed a marked increase in the surface area of tachyzoites during infection, indicating that tachyzoites invade their host cell and form their own compartments (PV) in which tachyzoites proliferate with a generation time of 24 h, eventually leading to cell rupture and exit of the parasites. A decrease was noted in the TEER of infected cells compared to uninfected controls, indicating that the invasion of the HBMECs by T. gondii had detectable effects on the integrity HBMECs monolayer by increased tight junction permeability. Morphological analysis revealed that the intracellular development of the tachyzoites disruption of tight junctions HBMECs monolayer and reorganization of some organelles of the host cell, such as the mitochondria, endoplasmic reticulum, and Golgi apparatus around the Parasitophorous vacuole membrane (PVM) and remained stable throughout the growth of the tachyzoites. The tight association between the PVM and host organelles may provide lipids and other macromolecules for parasite survival, proliferation, membrane biogenesis, and energy requirement. A marked decrease was noted in cell viability of infected cells at 48 h PI, compared to uninfected controls by alamar blue assay, indicating that growth of the parasites that cause a metabolic burden on the host cells. Metabolite analysis of HBMECs infected with T. gondii revealed a drastic increase in lactate and glutamine levels, as well as a reduction in choline and myo-inositol levels with infection. A drastic increase in lactate and glutamine levels may be attributed to the fact that T. gondii requires energy from the host, primarily via glycolysis and glutaminolysis. It is believed that increased lactate and glutamine levels result in increased paracellular permeability. A drastic reduction in choline and myo-inositol levels suggests the use of host lipid fractions for increased membrane maintenance or parasite lipid anabolism. It is believed that increased phosphatidylcholine levels result in altered monolayer permeability.